2014
DOI: 10.1002/bin.1386
|View full text |Cite
|
Sign up to set email alerts
|

Adherence to Discrete‐trial Instruction Procedures by Rural Parents of Children With Autism

Abstract: Parents of children with autism spectrum disorders may not attempt treatment, even when effective treatment options are available. Little is known about how to improve frequency of attempts to implement treatment (‘treatment adherence’). We provided 32 rural parents of young children with autism spectrum disorders with either written or video training materials about how to implement discrete‐trial instruction and compared parental adherence between the written (control) and video (experimental) groups. Parent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 50 publications
0
11
0
Order By: Relevance
“…The 7 studies included 1 quasi-experimental design by St. Peter et al [ 46 ], 1 nonconcurrent multiple-baseline designs by Wacker et al [ 47 ], 2 single-subject multiple-baseline design by Vismara et al [ 12 , 48 ], 1 RCT each by Ingersoll et al [ 44 ] and Pickard et al [ 45 ], and 2 prepost test design studies by Hamad et al [ 49 ] and Heitzman-Powell et al [ 50 ]. A lack of control groups in 5 of the 7 studies precluded the ability to conduct a meta-analysis of the results.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The 7 studies included 1 quasi-experimental design by St. Peter et al [ 46 ], 1 nonconcurrent multiple-baseline designs by Wacker et al [ 47 ], 2 single-subject multiple-baseline design by Vismara et al [ 12 , 48 ], 1 RCT each by Ingersoll et al [ 44 ] and Pickard et al [ 45 ], and 2 prepost test design studies by Hamad et al [ 49 ] and Heitzman-Powell et al [ 50 ]. A lack of control groups in 5 of the 7 studies precluded the ability to conduct a meta-analysis of the results.…”
Section: Resultsmentioning
confidence: 99%
“…The studies by Hamad et al [ 49 ], Heitzman-Powell et al [ 50 ], Vismara et al [ 12 , 48 ], and Wacker et al [ 47 ] demonstrated level IV evidence. The study by St. Peter et al [ 46 ] demonstrated level III-1 evidence and the study by Ingersoll et al [ 44 ] and Pickard et al [ 45 ] was classified as level II [ 43 - 45 ] evidence as per the NHMRC level of evidence guidelines (see Table 2 ) [ 41 ]. The low level of evidence may indicate that it is difficult to conduct research with this population due to travelling distance to research centers and reachability through recruitment strategies, thus making robust study designs more challenging.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Use of parents as therapists is not without obstacles. In a study of parental compliance in giving therapy to their ASD children, 31 no parent was found to be 100% compliant. Therapy recommended by the orthoptic department to be completed at home may therefore have a low compliance rate.…”
Section: Utilising Caregivers As Therapistsmentioning
confidence: 99%
“…Second, the cost of hiring a coach can be disproportionately burdensome to early education centers that serve children from low socioeconomic status families. And third, coaches are not always available in rural areas (Connell, Sanders, & Markie-Dadds, 1997;NICHD, 2002;St. Peter, et al, 2014).…”
Section: Introductionmentioning
confidence: 99%